Videoconferences and education - Zekanović-Korona, Ljiljana (Array, 2005)
The videoconferences find their application in different fields of the human activity: they enable us a higher quality of education, save our time and reduce our travel expenses. The aim of this research was to find out just how popular they are as means of education, how frequent is their use in education and how often and when are they desirable and applicable in education. The research was carried out with the subjects who have had an opportunity to use videoconference in education. The questionnaire was filled in also by teachers, whose opinion of videoconferences was also statistically elaborated. The further data analysis has included different statistic procedures used to analyse when and how a videoconference can be successfully used in education as a new educational technology.